2016
DOI: 10.1016/j.neuropharm.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-facetted impulsivity following nigral degeneration and dopamine replacement therapy

Abstract: Impulse control disorders (ICDs) are debilitating side effects of dopamine replacement therapy (DRT) in Parkinson’s disease (PD) that severely affect the quality of life of patients. While DRT, the pattern and extent of neurodegeneration, and prodromic factors of vulnerability (e.g. impulsivity) have all been hypothesized to play a role in the development of ICDs, their respective, and potentially interacting, contributions remain to be established. High impulsive (HI), Intermediate (Int) or low impulsive (LI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…In rats, alpha-synuclein induced nigrostriatal neurodegeneration increased waiting impulsivity and impulsive action. Pramipexole increased waiting impulsivity and impulsive action both in sham and lesioned rats but its effect on waiting impulsivity in lesioned rats was enhanced in animals with pre-existing impulsivity traits 105 . However, in contrast to impairments in decisional impulsivity in humans, studies either did not detect impairments 93 or showed improvement 106 in motor response inhibition in PD+ICD subjects tested using the stop signal task.…”
Section: Risk and Uncertaintymentioning
confidence: 84%
“…In rats, alpha-synuclein induced nigrostriatal neurodegeneration increased waiting impulsivity and impulsive action. Pramipexole increased waiting impulsivity and impulsive action both in sham and lesioned rats but its effect on waiting impulsivity in lesioned rats was enhanced in animals with pre-existing impulsivity traits 105 . However, in contrast to impairments in decisional impulsivity in humans, studies either did not detect impairments 93 or showed improvement 106 in motor response inhibition in PD+ICD subjects tested using the stop signal task.…”
Section: Risk and Uncertaintymentioning
confidence: 84%
“…By contrast, pramipexole was not associated with changes in compulsivity. Similarly, α-synuclein-induced nigrostriatal neurodegeneration increases impulsivity by itself, subsequent chronic pramipexole administration exacerbating it (Engeln et al, 2016). Impulsive behavior does not develop in 6-OHDA-lesioned rodents (Baunez and Robbins, 1999;Carvalho et al, 2017).…”
Section: Impulse Control Disordersmentioning
confidence: 99%
“…Compulsive, intermediate and non-compulsive (NC) animals were identified using a two-step K-mean cluster analysis of the number of completed seeking-taking cycles during the last 3 days of the seeking-taking punishment schedule (footshock intensity 0.45 mA; three data points per rat were considered). Cluster analysis has been shown to be a convenient and commonly used method for identifying objectively homogenous groups of objects within a data set (Tye et al, 2010;Murray et al, 2015;Engeln et al, 2016). Thus, the hypothesis-driven k-means clustering with maximization of distance between groups defined a priori as 3 was performed on a unique dimension (compulsivity) but in a three-dimensional space (repeated measures).…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…By contrast, a subpopulation of rats maintained their seeking response despite punishment, thereby displaying compulsive alcohol seeking behavior (Figure 2a and b). A cluster analysis (Tye et al, 2010;Murray et al, 2015;Engeln et al, 2016) performed on the completed seeking-taking cycles during the last 3 sessions of punishment (Supplementary Figure S3) confirmed the existence of three subgroups of rats: 34% of the population displayed compulsive alcohol seeking (compulsive, C, rats, n = 21), whereas, unexpectedly, a 30% sub-population greatly suppressed their seeking responses (NC rats, n = 18); 36% of the population (intermediate, I, rats, n = 22) between C and NC rats partially suppressed seeking when intermittently punished (compulsivity: F 2,55 = 84.55, po0.001, η 2 = 0.75 and time × compulsivity: F 18,495 = 16.75, po0.001, η 2 = 0.38). These data demonstrate that the propensity to drink alcohol is clearly not sufficient to predict the transition to compulsive alcohol seeking behavior (see SOM).…”
Section: Characterization Of Compulsive Alcohol Seeking Behaviormentioning
confidence: 99%